PRESPEKTIF ALIRAN UTILITARIANISME DALAM HUKUM DAN KAITANNYA DENGAN PEMBERLAKUAN UU CIPTA KERJA - Imam Fawaid; Abd. Rahman Saleh (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Law is essentially about seeking truth and justice. With truth and justice, legal happiness will be created for those who seek legal justice. Law is synonymous with justice as a spatial solution in every law enforcement. The legal school of utilitarianism is one of the currents in legal philosophy. With legal happiness, society will feel comfortable accepting it. So the legal school of utilitarianism views the law as having to be happy. The Job Creation Law, which has caused many legal problems, was created to ensure happiness in every workforce management system. The legal space of utilitarianism becomes a legal space for happiness in the Job Creation Law. So that the legal school of utilitarianism becomes a solution to the legal deadlock in managing employment in employment practices.